Working with high-risk youth: a relationship-based practice framework - Smyth, Peter (Routledge, 2017)
Introduction: a relationship-based practice framework -- Where do high risk youth come from? Part A: the attachment perspective -- Where do high risk youth come from? Part B: the neuroscience perspective -- Why a harm reduction philosophy is essential for working with high risk youth -- Building from strengths and promoting resiliency -- Engaging community, engaging youth -- Getting connected: the profound importance of relationship -- Broken spirits: addictions with high risk youth -- Strategies for engaging and working with high risk youth -- No room for error: boundaries and ethics and high risk youth -- Conclusion: a reason for optimism